A cross-sectional study on knowledge, attitude and practices of medical doctors towards antibiotic prescribing patterns and resistance in Khyber Pakhtun Khawah, Pakistan - Maira Faizullah, Nisar-ur-Rahman, Muhammad Ihtesham Umar, Mudassir Anwar, Muhammad Sarfraz (Journal of Applied Pharmaceutical Science, 2017)
Irrational prescribing and resistance to antibiotics are major health concerns globally. The aim of this study was to assess the physicians’ knowledge, attitude and practice about antibiotic prescribing and resistance in Khyber Pakhtun Khawah (KPK), Pakistan. A cross-sectional, descriptive study was conducted using a pre-validated self-administered questionnaire. Statistical Package for Social Sciences (SPSS®) version 23 was employed to analyze the data. A total of 320 medical practitioners participated with a response rate of 61.5%. Participants generally had a good knowledge about antibiotic use. However, some flaws were observed in their practice. The Internet (96%), antibiotic guidelines (92%) and medical representatives (85.9%) were reported to be the most useful sources of information. More than 70% of the respondents cited patient demand as one of the major reasons for antibiotic overuse. Antibiotic resistance was reported to be due to the failure to complete the antibiotic course by 94.1% of the respondents. The majority of the participants never had a training on the rational use of antibiotics and were in a favour of attending such training if offered. The study concluded that there is a dynamic need of training initiatives for improving antibiotics prescribing behaviour of general practitioners through the development of local guidelines and continuous education of general practitioners to promote rational antibiotic prescribing.
Keywords: Antibiotic resistance, Rational antibiotic use, Physicians’ knowledge, Pakistan.